Antihypertensive medications and cancer risk: Evidence from 0.27 million patients with newly diagnosed hypertension - Yu, Huan; Liu, Zhike; Wu, Yiqun; Zheng, Liuyan; Wang, Kun; Wu, Jingxian; Wang, Huairong; Ding, Kexin; Yang, Ruotong; Zhou, Huziwei; Sun, Feng; Hu, Yonghua; et al. (Frontiers in Pharmacology, 2025)
BackgroundWhether specific antihypertensive treatments increase cancer risk in patients with hypertension is still controversial. We aimed to estimate the associations of different antihypertensive treatments with cancer risk in real-world settings.MethodsA longitudinal cohort study was designed in a population of 1.2 million individuals from the CHinese Electronic health Records Research in Yinzhou (CHERRY). Propensity score matching (PSM) and the Cox regression model were used to estimate the associations. Several sensitivity analyses were then performed to reduce potential residual confounding.ResultsFrom 2009 to 2019, a total of 270,320 patients with newly diagnosed hypertension were included in this study. With a median follow-up time of 7.7 years, 14,264 cases of cancer occurred. There were no significant associations of angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), β-blockers, or thiazide diuretics (TDs) with cancer risk (p > 0.05). Compared with other antihypertensive treatments, the use of calcium channel blockers (CCBs) was significantly associated with a marginally mild increase in the risk of all cancers (hazard ratio, HR = 1.05; 95% CI: 1.01, 1.09; p = 0.017). However, this association was no longer observed in sensitivity analyses excluding patients with less than 1, 2, or 3 years of follow-up. Nevertheless, the association between CCBs and the risk of endocrine cancer, especially thyroid cancer, still exists.ConclusionDespite previous controversy, in this study, we found no clinically meaningful cancer risk associated with antihypertensive medications. However, the association of CCBs with specific cancer still requires further research. These findings should be interpreted with caution due to the potential residual confounding.